1997
DOI: 10.2337/diacare.20.11.1693
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) in Android Obesity and NIDDM

Abstract: Lp(a) levels are significantly elevated in both android-obese and nonobese NIDDM patients regardless of the degree of glycemic control. Lp(a) is an independent risk factor showing greater elevations in those subjects complicated with diabetic vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Cross-sectional studies of adults have not consistently shown a relationship of Lp(a) with NIDDM. Conversely, several reports indicate an association between IDDM with Lp(a) [29,41]. However, NIDDM is thought to have a stronger genetic component in its etiology than IDDM [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies of adults have not consistently shown a relationship of Lp(a) with NIDDM. Conversely, several reports indicate an association between IDDM with Lp(a) [29,41]. However, NIDDM is thought to have a stronger genetic component in its etiology than IDDM [42].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of serum Lp(a) is also associated with an increased risk of coronary heart disease in patients with diabetes [13,14]. It is also a predictor of non-proliferative retinopathy in these patients [15][16][17][18][19]. Lp(a) is present in the arterial wall at sites of atherosclerosis in humans and results in both atherogenesis and thrombosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Lp(a) is recognized as a new coronary risk factor, but few studies have quantitatively assessed the relationship of serum Lp(a) levels with other coronary risk factors in many patients undergoing coronary cineangiography. Among many coronary risk factors that were quantified (i.e., age, gender, hypertension, impaired glucose tolerance, cerebrovascular accident, hyperuricemia, smoking, family history of ischemic heart disease (IHD), history of hyperlipidemia, Lp(a), total cholesterol, high density lipoprotein (HDL)-cholesterol, triglyceride, low density lipoprotein-cho-lesterol, apo A-I,B, E), Lp(a) is an independent, potential, and modifiable coronary risk factor, and its reduction is important in the clinical management of patients with ischemic heart disease and stroke [8][9][10][11] . Newer risk factors were described, including homocysteine and chronic infection (Chlamydia pneumoniae and periodontal disease), are being studied as predictors of ischemic stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Prospective studies that evaluated Lp(a) as a predictor of cardiovascular and cerebrovascular events in men have had conflicting results . Some studies suggested that Lp(a) was an independent risk factor for coronary heart disease (CHD), while others showed no significant association [6][7][8][9][10][11][12] . Strokes are one of the most common causes of mortality and long term severe disability.…”
mentioning
confidence: 99%